Exploring the use of cognitive poetics in teaching literature: documenting teachers’ experience and classroom practices - Abdullah, Suhaila; Idrus, Faizah (2023)
This qualitative research studies teachers’ experience and common practices used for teaching literature for the past two years (2020-2022) and this research explores whether they could incorporate cognitive poetics in the teaching of literature in the classroom. The use of cognitive poetics in teaching literature in the classroom is the main area that is studied in this research and the researchers intend to find out if this approach could assist teachers in teaching this subject to facilitate students’ understanding of literary texts. This paper would like to shed findings on the common approaches that teachers used to draw students’ attention to studying literary works. The implication of this research is to answer the questions whether the common approaches and the additional approach of using cognitive poetics in the teaching of literature could further support thinking skills for secondary school students in Malaysia and to fulfil the goals of attaining HOTS (Higher Order Thinking Skills) in the curriculum set by the Ministry of Education, Malaysia.